2008
DOI: 10.1073/pnas.0711099105
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of mentalizing-related computations during strategic interactions in humans

Abstract: Competing successfully against an intelligent adversary requires the ability to mentalize an opponent's state of mind to anticipate his/her future behavior. Although much is known about what brain regions are activated during mentalizing, the question of how this function is implemented has received little attention to date. Here we formulated a computational model describing the capacity to mentalize in games. We scanned human subjects with functional MRI while they participated in a simple two-player strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
558
4
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(615 citation statements)
references
References 33 publications
52
558
4
1
Order By: Relevance
“…Other authors have similarly described the DMPFC as a key region where self-referential processing and perspective-taking interact (D'Argembeau et al 2007) or where self-relevance in interpersonal contexts is represented (Schilbach et al 2006). These findings therefore add to previous attempts to disentangle the differential contributions of subregions within the ToM network to different psychological processes involved in ToM capabilities (Saxe 2006;Ciaramidaro et al 2007;Hampton et al 2008;Jenkins and Mitchell 2010), suggesting that the temporal and parietal parts of this network may represent the mental states, attributes, and/or intentions of others, while the frontal part in the paracingulate cortex may connect these representations with those related to the self, consistent with evidence for a particular involvement of this area in social tactics (Fukui et al 2006). This interpretation is in line with the recent proposal by Saxe (2006) that the TPJ supports the human ability to reason about the content of mental states, while the DMPFC is involved when the self must coordinate his/her own current goal or focus of attention with another person.…”
Section: Discussionsupporting
confidence: 55%
“…Other authors have similarly described the DMPFC as a key region where self-referential processing and perspective-taking interact (D'Argembeau et al 2007) or where self-relevance in interpersonal contexts is represented (Schilbach et al 2006). These findings therefore add to previous attempts to disentangle the differential contributions of subregions within the ToM network to different psychological processes involved in ToM capabilities (Saxe 2006;Ciaramidaro et al 2007;Hampton et al 2008;Jenkins and Mitchell 2010), suggesting that the temporal and parietal parts of this network may represent the mental states, attributes, and/or intentions of others, while the frontal part in the paracingulate cortex may connect these representations with those related to the self, consistent with evidence for a particular involvement of this area in social tactics (Fukui et al 2006). This interpretation is in line with the recent proposal by Saxe (2006) that the TPJ supports the human ability to reason about the content of mental states, while the DMPFC is involved when the self must coordinate his/her own current goal or focus of attention with another person.…”
Section: Discussionsupporting
confidence: 55%
“…This study illustrates the conceptual and methodological advantages of an interdisciplinary approach and provides a novel quantitative framework to conceptualize the notion of trustworthiness as well as an approach to bridge the division between descriptive information and experienced information in the judgment and decision-making literature (Jessup et al, 2008). More broadly, our study provides an important and timely contribution to a growing literature interested in the neural computations underlying social learning (Behrens et al, 2008;Biele et al, 2009;Delgado et al, 2005;Hampton, Bossaerts, & O'Doherty, 2008;King-Casas et al, 2005;Olsson & Phelps, 2007) and trustworthiness (Krueger et al, 2007;Oosterhof & Todorov, 2008;van 't Wout & Sanfey, 2008;Winston, Strange, O'Doherty, & Dolan, 2002) and illustrates the importance of social beliefs in decision-making behavior.…”
Section: Resultsmentioning
confidence: 73%
“…However, some recent studies have begun to use modeling in conjunction with behavior to better understand how social decision-making develops. For example, one experiment (Hampton, Bossaerts, & O'Doherty, 2008) used computational modeling to provide insight into the process of mentalizing about another player's strategy in a game known as the Inspection Game. Additionally, Apesteguia, Huck, and Oechssler (2007) demonstrated that when given the opportunity to view other player's behavior in a game, people will often imitate the strategy that provides the highest payoff.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative may be to draw on research in neuroeconomics and develop a model of the human‐VC behaviour in which the values and rewards that the human and VC assign to different options can be modelled on a trial‐by‐trial basis (Hampton et al ., 2008). However, for complex negotiations, there may not be suitable models available.…”
Section: The Munros – Challenges In the Implementation Of Vrmentioning
confidence: 99%